Indonesia-Japan Cooperation in Labour Migration to Improve the Competitiveness of Indonesian Migrant Workers - Sumiati, Encum (International Journal Labs, 2022)
The 2018 Global Compact of Migration provides guidance for countries informulating policies and actions to improve the quality of International Migration governance so that they can realize migration that benefits Indonesian Migrant Workers, sending countries, and receiving countries. This research aims to analyze the cooperation of Indonesia and Japan in labour migration to improve the competitiveness of indonesian migrant workers. This research uses qualitative research methods which are carried out based on the interpretation of research data into research results. The research is carried out based on a review of official documents from authorized and relevant government agencies, experiences of actors in Indonesia-Japan cooperation in labor migration in the global labor market and studies references. Indonesia conducts bilateral relations with Japan under an economic cooperation agreement by sending Indonesian workers BNP2TKI as government representatives assigned to supervise the debriefing and protection of Indonesian workers. While on the Japanese side there is the Japan International Corporation of Welfare Services (JICWELS) which will be responsible for receiving the Indonesian Workforce.